Efektownie czy efektywnie? Analiza wizualnych właściwości podręczników do edukacji wczesnoszkolnej w kontekście rekomendacji poznawczych teorii uczenia się - Małgorzata Ciesielska (Problemy Wczesnej Edukacji)
Textbooks have for years held a dominant position among the teaching resources used in the education system, being so common that it is difficult to imagine a school without them. Research on textbooks has scarcely addressed their visual layer, often recognising that the greatest influence on the effectiveness of these materials is the content and the method adopted. However, research conducted within the framework of the cognitive load theory and the cognitive theory of multimedia learning demonstrates that the visual form of educational materials can influence the effectiveness of learning, particularly for beginning learners. The article presents the results of an analysis of three paper textbooks and one e-book for early childhood education that are commonly used in Polish public schools. The text is also a form of reflection on the reason for the decrease in the level of design and the lack of interest in a scientific approach to textbook design.